The effect of risks on Malaysian banks profitability: the Islamic and conventional banks / Noralia Aznol ... [et al.] - Aznol, Noralia; Shahril Nizam, Alif Shahezzat; Ahmad, Wahida; Amran, Nur Hazimah (UiTM Press, 2024)
The banking sector in Malaysia has seen substantial changes since the global financial crisis, with a greater focus now being placed on the value of risk management. The study aims to examine the impact of internal and external bank risks on Malaysia’s profitability. Utilising unbalanced panel data from 2010 to 2022, it includes 29 banks, comprising 14 Islamic banks and 15 conventional banks. The random effect model is found to be the most appropriate for the full samples and Islamic banks, while the fixed effect model is the preferred choice for conventional banks. Notably, Islamic banks tend to be less profitable compared to conventional banks. Even though Islamic banks display lower profitability compared to conventional banks, they have greater resilience, and their profitability is less impacted during crisis periods compared to conventional banks. Stronger resilience in Islamic and conventional banks is important to ensure sustainability and profitability.